Control of Francisella tularensis Virulence at Gene Level: Network of Transcription Factors - Spidlova, Petra; Stojkova, Pavla; Sjöstedt, Anders; Stulik, Jiri (Microorganisms, 2020)
Regulation of gene transcription is the initial step in the complex process that controls gene expression within bacteria. Transcriptional control involves the joint effort of RNA polymerases and numerous other regulatory factors. Whether global or local, positive or negative, regulators play an essential role in the bacterial cell. For instance, some regulators specifically modify the transcription of virulence genes, thereby being indispensable to pathogenic bacteria. Here, we provide a comprehensive overview of important transcription factors and DNA-binding proteins described for the virulent bacterium Francisella tularensis, the causative agent of tularemia. This is an unexplored research area, and the poorly described networks of transcription factors merit additional experimental studies to help elucidate the molecular mechanisms of pathogenesis in this bacterium, and how they contribute to disease.
Keywords: virulence; transcription factor; pathogenesis; Francisella; gene regulation